Lili Dujourie - Folds in time - Van Cauteren, Philippe 1969-; Bossche, Phillip van den; Germann, Martin 1974-; Folie, Sabine 1962-; Verhelst, Peter 1962- (König, 2015)
"Like the exhibition, this book is conceived in two parts. The first part is composed entirely of text - written in Dutch - with one exception, the fragment of Van Eyck's masterpiece. The second part is the one you're holding in your hands. This English version acts as the third 'exhibition space'. Dirk Pauwels, S.M.A.K.'s in-house-photographer, has taken pictures of Lili Dujourie's works in both museums in close collaboration with the artist" (Introduction)
Published on the occasion of the exhibition "Lili Dujourie - Folds in time", S.M.A.K. Ghent, Mu.Zee Ostend, June 6 - October 4, 2015
Keywords: Dujourie, Lili -- 1941-; (Produktform)Book; Malerei; Skulptur; SMAK Gent; (VLB-WN)1583: Hardcover, Softcover / Kunst/Bildende Kunst; Plastik; Feminismus; Installation -- Kunst; Ausstellungskatalog -- S.M.A.K. -- 06.06.2015-04.10.2015 -- Gent; Ausstellungskatalog -- Mu.ZEE -- 06.06.2015-04.10.2015 -- Ostende